Scolariser un élève en situation de handicap, la question de l'attention conjointe en classe - Valérie Vilaine (Recherches en Éducation)
We are interested in the schooling of a student with autism spectrum disorder in year 5 (CM1) class, supported by a localized unit for school inclusion (ULIS). The study concerns more precisely the presence of this student in the creation and realization of a collective work in dance. We are looking for the conditions under which the joint attention of the teacher and the students to the movement danced together allows to increase the quality of his presence in dance. Our didactic research is part of a cooperative engineering between teachers and researcher. The collective thus conceives a co-teaching in situ in order to create didactic situations favorable to schooling. We describe the concrete of the classroom from episodes selected from study films. The observational data are worked on from the notions of contract and environment within the framework of the theory of joint action in didactics (TACD).